Pengaruh Political Connection dan Managerial Ownership terhadap Tax Aggressiveness - Firma Ayu Diafitri; Herlina Helmy (Universitas Negeri Padang, 2023)
The aim of this research is to examine effect of political connection and managerial ownership on tax aggressiveness in primary consumer goods manufacturing companies listed on Indonesia Stock Exchange 2019-2021. The type of this research is causative research, with purposive sampling technique, it got 38 companies as sample. The researcher applied multiple regression analysis. While, the result showed that a political connection had significant and positive effects on tax aggressiveness, while managerial ownership had not significant effects on tax aggressiveness.